Health-promotion and health-harming behaviours in pregnant women: role of coping strategies, anxiety, and depression. (3rd April 2022) - Pasha, Hajar; Faramarzi, Mahbobeh; Chehrazi, Mohammad; Bakouei, Fatemeh; Gholinia, Hemmat; Abdollahi, Somayeh; Shafierizi, Shiva
Abstract: There is a lack information on psychological predictors of health-promotion and health-harming behaviours during pregnancy. The study aimed to examine whether psychological factors including anxiety, depression, and coping strategies could predict the health-promotion and health-harm behaviours of pregnant women. In a cross-sectional study 200 pregnant women with singleton pregnancies, older than 18 years, and with at least 5 years of education were enrolled. The participants completed four questionnaires during their prenatal care appointments. The questionnaires included the prenatal health behaviour scale (PHBS), Revised Prenatal Coping Inventory (NU-PCI), Beck Depression Inventory (BDI-II), and State-Anxiety Inventory. The results revealed that planning-preparation coping was a strong positive independent variable associated with healthy behaviours (health-promoting behavioural/nutrition (β = 0.800, p  = .001); health-promoting physical activity ( β  = 0.191, p  = .049)). It was negatively associated with unhealthy behaviours (health-harming behavioural/nutrition ( β  = 0.290, p  < .001) as well as health-harming physical activity (β = −0.290, p  = .010)). Anxiety was significantly associated negatively with healthy behaviours. Depression was the strongest positive independent variable correlated with health-harming behavioural/nutrition ( β  = 0.290, p  < .001). Finally, avoidance coping ( β  = 0.179, p  = .037) was significant for health-harming physical activity. Impact statement: What is already known on this subject? Previous studies have shown that there is a correlation between psychological factors and healthy behaviours of pregnant women. What do the results of this study add? The findings highlight the significant roles of coping strategies, anxiety, and depression for predicting healthy or unhealthy behaviours of pregnant women. What are the implications of these findings for clinical practice and/or further research? The findings implied that pregnant women who use more adaptive coping strategies, especially planning- preparing coping, reported lower levels of anxiety/depression and engaged more in healthy behaviours. The study also suggests that obstetricians and health care providers should pay more attention to the roles of coping strategies, especially planning-preparation and avoidance coping, anxiety, and depression in improving health-promotion/health-harming behaviours of pregnant women.